WHITE MATTER DAMAGE AFTER TRAUMATIC BRAIN INJURY: A ROLE FOR DAMAGE ASSOCIATED MOLECULAR PATTERNS - Braun, Molly (Biochim Biophys Acta, 2017)
Traumatic brain injury (TBI) is a leading cause of mortality and long-term morbidity worldwide. Despite decades of pre-clinical investigation, therapeutic strategies focused on acute neuroprotection failed to improve TBI outcomes. This lack of translational success has necessitated a reassessment of the optimal targets for intervention, including a heightened focus on secondary injury mechanisms. Chronic immune activation correlates with progressive neurodegeneration for decades after TBI; however, significant challenges remain in functionally and mechanistically defining immune activation after TBI. In this review, we explore the burgeoning evidence implicating the acute release of damage associated molecular patterns (DAMPs), such as adenosine 5′-triphosphate (ATP), high mobility group box protein 1 (HMGB1), S100 proteins, and hyaluronic acid in the initiation of progressive neurological injury, including white matter loss after TBI. The role that pattern recognition receptors, including toll-like receptor and purinergic receptors, play in progressive neurological injury after TBI is detailed. Finally, we provide support for the notion that resident and infiltrating macrophages are critical cellular targets linking acute DAMP release with adaptive immune responses and chronic injury after TBI. The therapeutic potential of targeting DAMPs and barriers to clinical translational, in the context of TBI patient management, are discussed.